Traumatized child soldiers: Far away but not yet safe (KULT_online, 2016)
Dima Zito’s monograph Überlebensgeschichten. Kindersoldatinnen und –soldaten als Flüchtlinge in Deutschland demonstrates the significance of the traumatic experiences of child soldiers through excerpts and quotes from the traumatized interviewees. The traumatic experiences are framed by topical elaborations and the concept of sequential traumatization by Keilson. While this study can be seen as an attempt to structure the wide range of topics around the war traumata of children, it also provides, with its broad approach, a good introduction to this complex field of research.